Keanekaragaman Serangga Di Perkebunan Kakao (Theobroma cacao L.) Desa Juma Gerat Kecamatan Tigalingga Kabupaten Dairi - Chumaira Alfai Sembiring; Husnarika Febriani; Melfa Aisyah Hutasuhut (Journal of Natural Sciences, 2022)
Cocoa is a plantation crop that is favored by many types of insects, ranging from beneficial and harmful insects. This study aims to identify insects and determine the index of insect diversity found in the Cocoa Plantation in Juma Gerat Village, Tigalingga District, Dairi Regency. By using the purposive sampling method with the sampling technique using the Yellow Pan Trap and Yellow Sticky Trap methods. Insect sampling was carried out at 5 points of observation locations with 7 sampling times, on an area of 1 hectare. The results showed that there were 27 species of insects (Lepisiota sp., Anoplolepis gracilipes, Chelonus sp., Cremnops sp., Bactrocera dorsalis, Trigonocera rivosa, Brachycera sp., Culex Pipiens, Herina sp., Sambio sp., Atherigona rodani, Cafius sp., Aphodius rudicola, Calleida letreille, Oides palleata, Paropsisterna sp., Merdilina pustulata, Helopeltis sp., Bhandara translucida, Deselvana simulans, Bothrogonia addita, Palanococcus citri, Italochrysa sp., Gryllus aptera, Periplaneta sp., Blatella germanica, Chilo sp.). The cocoa insect diversity index in Juma Gerat Village is categorized as medium with a value of 1,528, and the Dominance Index of 0,326 is categorized as low. This value indicates that there is no type of insect that dominates and the distribution of insect species is evenly distributed in the area.